Genetic diversity and geographic relationships amongst southern African Amblyomma ticks, Rickettsia africae and Ehrlichia ruminantium - Neves, Luís C.B.G. (University of Pretoria, 2024)
Thesis (PhD (Veterinary Science))--University of Pretoria, 2024.